Scandal or Sex Crime? Ethical Implications of the Celebrity Nude Photo Leaks - Marwick, Alice E. (AoIR Selected Papers of Internet Research, 2016)
This paper explores the ethical frames and implications of the 2014 leak of a large archive of digital photos of primarily female celebrities known as "Celebgate" or "the Fappening." These photos, mostly scantily clad or nude selfies taken with iPhones, were stolen from Apple's iCloud servers and posted on image sharing board 4Chan and then to Reddit. The leak garnered an immense amount of publicity, significant revenue for Reddit, and an intense public discussion around the ethics of viewing and sharing the images. This paper is grounded in the emerging feminist literature on geek masculinity, gendered harassment, and misogynist subcultures online, and uses critical discourse analysis to examine how Redditors framed and made meaning of the nude photo leaks. I present selections from a mass capture of 94,602 text comments from reddit.com/r/thefappening. These comments are augmented by a discourse analysis of popular press discussion, primarily from afflicted celebrities, feminist columnists, and journalists. I analyze US legal policy around celebrity privacy to discuss the “need to know, right to know, want to know” ethical framework that has been used to justify publicizing private information. I conclude that the potential for attention and publicity brought about by the material affordances of the modern internet creates a continuum between “celebrities” and “average people.” Thus, attitudes towards nude photos of celebrities may mirror public attitudes towards stolen photos of the non-famous, such as revenge porn.